Method for reducing structural deformation and damage of silicon-based anode in circulation process

By using Ti3C2Tx MXene&SGC composite material as the silicon-based anode active material, the problem of structural deformation and damage of the silicon-based anode during the cycle is solved, and the longer cycle life and more stable electrochemical performance of the battery are achieved.

CN119481069APending Publication Date: 2025-02-18JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411855476.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Silicon-based anode is prone to structural deformation and damage during the circulation of lithium-ion batteries, resulting in short cycle life of the battery and unstable electrochemical performance.

Method used

Ti3C2Tx MXene&SGC composite material is used as the silicon-based anode active material, and Ti3C2Tx MXene&SGC composite material is formed through the design of the layered structure and nanosheet coating to reduce structural deformation and damage.

Benefits of technology

It effectively reduces the structural deformation and damage of the silicon-based anode during the circulation process, improves the cycling performance and electrochemical stability of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of silicon-based anode materials, in particular to a method for reducing structural deformation and damage in the circulation process of a silicon-based anode. The preparation method comprises the following steps: adopting Ti < 3 > C < 2 > T < x > MXeneamp; the SGC composite material is used as a silicon-based anode active material; the Ti < 3 > C < 2 > T < x > M < X > eneamp; the preparation method of the SGC composite material comprises the following steps: (1) dispersing nano silicon into phenolic resin, then enabling the nano silicon and graphene oxide to be adsorbed and self-assembled to form gel by utilizing a surface charge adsorption effect, and then performing freeze drying, grinding, carbonization treatment and CVD treatment to obtain the SGC composite material; (2) the surface of the SGC composite material is coated with the Ti < 3 > C < 2 > T < x > MXene nanosheets in a vacuum suction filtration mode, and Ti < 3 > C < 2 > T < x > MXene amp is obtained; the invention discloses an SGC composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicon-based anode materials, and in particular to a method for alleviating structural deformation and damage during the circulation process of silicon-based anodes. Background Art

[0002] Lithium-ion batteries are currently the batteries with the highest specific energy density, but compared with traditional cars equipped with internal combustion engines, the driving range of lithium-ion battery electric vehicles is limited. The reason is that the vast majority of existing lithium-ion batteries use graphite as the negative electrode, LiMO x (M stands for transition metal) As the positive electrode, this type of traditional lithium-ion battery graphite negative electrode material has a limited theoretical specific capacity of only about 370mAh g −1 , which cannot meet the high energy density demand of the advanced electric and hybrid vehicle markets. The storage capacity of lithium-ion batteries mainly depends on the specific capacity of positive and negative electrode materials. Therefore, with the development of technology, people's demand for high-capacity energy storage materials will also increase.

[0003] Silicon-based anode materials have attracted widespread attention as alternative anode materials for lithium-ion batteries, mainly because of their specific capacity of 3579 mAh g -1 , volume capacity is 9786mAh·cm -3 , the working potential is relatively low (compared to Li / Li + Compared with lithium, silicon is about 0.5V), and silicon is naturally abundant and harmless to the environment. However, before large-scale commercial application, silicon-based negative electrode materials face some challenging problems, such as large capacity decay, short cycle life, and excessive volume expansion (over 300%) during the alloying process with lithium, which leads to pulverization of active material particles in the electrode and even peeling off from the electrode. So far, people have been working hard to improve the electrochemical performance of silicon-based anodes.

[0004] In summary, the present invention proposes a method for reducing structural deformation and damage during the cycle of silicon-based anodes, which is of great significance. Summary of the invention

[0005] The object of the present invention is to provide a method for alleviating structural deformation and damage during the circulation process of a silicon-based anode, so as to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions: A method to reduce structural deformation and damage during the cycling of silicon-based anodes by using Ti3C2T x MXene&SGC composites are realized as silicon-based anode active materials.

[0007] Furthermore, the Ti3C2Tx The MXene&SGC composite material has a layered structure, with Ti3C2T x MXene substrate, SGC interlayer and Ti3C2T x The top three-layer structure of MXene.

[0008] Furthermore, the Ti3C2T x The preparation method of MXene&SGC composite material is as follows: (1) dispersing nano-silicon into phenolic resin, and then utilizing the surface charge adsorption effect to make nano-silicon and graphene oxide adsorb and self-assemble to form gel, and then freeze-drying, grinding, carbonization treatment, and CVD treatment to obtain SGC composite material; (2) vacuum filtration is used to make Ti3C2T x MXene nanosheets were coated on the surface of SGC composites to obtain Ti3C2T x MXene&SGC composite materials.

[0009] Furthermore, the Ti3C2T x The preparation method of MXene&SGC composite material specifically comprises the following steps: S1: slowly add 2-pentanol and 1,2-bis[(dimethylamino)dimethylsilyl]ethane to N-methylpyrrolidone, and stir and mix for 15 to 60 minutes to prepare a mixed solution I; S2: adding nano silicon to the mixed solution I, stirring and mixing for 1 to 3 hours to prepare a modified silicon dispersion; S3: adding phenolic resin to N-methylpyrrolidone, stirring to dissolve, and preparing a phenolic resin solution; S4: mixing the modified silicon dispersion and the phenolic resin solution, stirring evenly, to prepare a mixed solution II; S5: adding graphene oxide to N-methylpyrrolidone, stirring and mixing for 1-3 hours, and preparing a 3-3.5 wt % graphene dispersion; S6: slowly adding the graphene dispersion into the mixed solution II to prepare a mixed solution III, and then freeze-drying the mixed solution to obtain an aerogel; S7: grinding the aerogel into a powder of 150-220 mesh to obtain a precursor powder; S8: placing the precursor powder into a tube furnace, and subjecting the precursor powder to carbonization treatment and CVD treatment to obtain an SGC composite material; S9: Ti3C2T x MXene nanosheets were added to N-methylpyrrolidone and stirred for 1-3 hours to prepare 4-6 mg / mL Ti3C2T x MXene dispersion; S10: Take part of Ti3C2T x The MXene dispersion was dried and deposited by vacuum filtration to obtain Ti3C2T x MXene substrate; S11: adding the SGC composite material into deionized water, and ultrasonically dispersing for 10-20 minutes to prepare an SGC dispersion; S12: Apply SGC dispersion evenly to Ti3C2T x On the MXene substrate layer, it is dried and deposited by vacuum filtration to obtain the SGC intermediate layer; S13: Take another Ti3C2T with the same volume as that in S10 x The MXene dispersion was evenly coated on the SGC middle layer and dried and deposited by vacuum filtration to obtain Ti3C2T x MXene top layer; get Ti3C2T x MXene&SGC composite materials.

[0010] Furthermore, the volume ratio of the 2-pentanol, 1,2-bis[(dimethylamino)dimethylsilyl]ethane and N-methylpyrrolidone is 1:2:9.

[0011] Furthermore, the ratio of the nano-silicon to the mixed solution I is 1 g:10 mL.

[0012] Furthermore, the particle size of the nano-silicon is 100 nm.

[0013] Furthermore, the mass ratio of the nano-silicon, graphene oxide and phenolic resin is 10:1:25.

[0014] Furthermore, the freeze-drying treatment is as follows: placing the mixed solution III into a freeze dryer and freeze-drying it at -35 to -25°C for 5 to 10 days.

[0015] Furthermore, the specific process of the carbonization treatment is: placing the precursor powder in a tubular furnace filled with argon (Ar), heating from room temperature to 480-520° C. at a heating rate of 5° C. / min for 1-3 hours.

[0016] Furthermore, the specific process of the CVD treatment is as follows: after the carbonization treatment, an Ar / CH4 mixed gas is introduced into the tubular furnace, and then the temperature is continuously increased to 850-900°C at a heating rate of 2°C / min for 1-3h.

[0017] Furthermore, the Ar / CH4 mixed gas is composed of Ar and CH4 mixed in a volume ratio of 1:1.

[0018] Furthermore, in S10 and S13, the Ti3C2T x The mass ratio of MXene nanosheets to SGC composites is 1:4.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The synthesis path of SGC composite materials is simple, avoiding tedious treatments such as high temperature drying and acid-base treatment, which is conducive to saving experimental costs; 2. Ti3C2T x MXene nanosheets can further provide a layer of protection for SGC composite materials and reduce the damage caused by volume expansion. At the same time, it can also reduce the breakage and repair process of SEI film and ensure the stability of SEI film. In addition, it can also provide excellent mechanical toughness to protect silicon-based anode materials, thereby increasing the strength and stability of the battery and preventing structural deformation and damage of the battery during the cycle. 3. Ti3C2T prepared by the present invention x MXene&SGC composite materials have a porous structure, which can effectively improve the cycle performance of the material. The combination of graphene and porous silicon is conducive to reducing polarization during the cycle process, and the dense carbon film on the surface can effectively block the direct contact between nano-silicon and the electrolyte, avoiding the cyclic iterative growth of the SEI film.

[0020] In summary, the Ti3C2T prepared by the present invention x MXene&SGC composite materials can reduce the structural deformation and damage of silicon-based anodes during the cycle process, while also reducing the breakage and repair process of the SEI film and protecting the stability of the SEI; as a silicon-based anode active material, it can greatly improve the electrochemical performance of the battery and has important practical significance. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] It should be noted that the purchasers of all raw materials involved in the present invention include, without any special restrictions, illustratively: 2-Pentanol with a purity of 99% and N-methylpyrrolidone with a purity of 99% were purchased from Shanghai Jinjinle Industrial Co., Ltd.; 1,2-Bis[(dimethylamino)dimethylsilyl]ethane with a purity of 99%, CAS number: 91166-50-6, purchased from Shanghai Bid Pharmaceutical Technology Co., Ltd.; Nano-silicon, particle size 100 nm, purchased from Hunan Zhongke Xingcheng Graphite Co., Ltd.; Phenolic resin, model PR, solid content 30wt%, purchased from SQ Group; Graphene oxide, single layer, thickness 0.55~1.2nm, sheet diameter 0.5~3μm, catalog number: G139803, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Ti3C2T x MXene nanosheets, model ZKK01, sheet diameter 2 μm, thickness 100 nm, purchased from Beijing Dekedaojin Technology Co., Ltd.; Commercial silicon carbon powder was purchased from Jinhua Alloy Co., Ltd.

[0023] Example 1: A method for reducing structural deformation and damage during the cycle of silicon-based anodes: S1: 10 mL of 2-pentanol and 20 mL of 1,2-bis[(dimethylamino)dimethylsilyl]ethane were slowly added to 90 mL of N-methylpyrrolidone, and the mixture was stirred for 30 min to prepare a mixed solution I; S2: Add 12 g of nano silicon into the mixed solution I, stir and mix for 2 h to prepare a modified silicon dispersion; S3: adding 30 g of phenolic resin to an appropriate amount of N-methylpyrrolidone, stirring to dissolve, and preparing a phenolic resin solution; S4: mixing the modified silicon dispersion obtained in S2 and the phenolic resin solution obtained in S3, stirring them evenly to obtain a mixed solution II; S5: adding 1.2 g of graphene oxide to N-methylpyrrolidone, stirring and mixing for 2 h, to obtain a 3.3 wt % graphene dispersion; S6: slowly adding the graphene dispersion obtained in S5 to the mixed solution II obtained in S4 to obtain a mixed solution III (ensuring that the mass ratio of nano-silicon, graphene oxide and phenolic resin in the mixed solution III is 10:1:25), then placing the mixed solution III in a freeze dryer and freeze-drying it at -30°C for 7 days to obtain an aerogel; S7: grinding the aerogel obtained in S6 into a powder of 200 mesh to obtain a precursor powder; S8: placing the precursor powder obtained in S7 in a tubular furnace filled with Ar, heating from room temperature to 500°C for 2h at a heating rate of 5°C / min to complete the carbonization treatment; then introducing Ar / CH4 mixed gas (volume ratio 1:1) into the tubular furnace, and then continuing to heat to 880°C at a heating rate of 2°C / min for 2h to complete the CVD treatment and obtain the SGC composite material; S9: 50 mg of Ti3C2Tx MXene nanosheets were added to N-methylpyrrolidone and stirred for 2 h to obtain 5 mg / mL Ti3C2T x MXene dispersion; S10: Take 5 mL of Ti3C2T obtained in S9 x The MXene dispersion was dried and deposited by vacuum filtration to obtain Ti3C2T x MXene substrate; S11: adding 200 mg of the SGC composite material into an appropriate amount of deionized water, and ultrasonically dispersing for 15 min to obtain an SGC dispersion; S12: Apply SGC dispersion evenly to Ti3C2T x On the MXene substrate layer, it is dried and deposited by vacuum filtration to obtain the SGC intermediate layer; S13: Take another 5 mL of Ti3C2T obtained in S9 x The MXene dispersion was evenly coated on the SGC middle layer and dried and deposited by vacuum filtration to obtain Ti3C2T x MXene top layer; get Ti3C2T x MXene&SGC composite materials.

[0024] Based on Example 1, a control experiment was carried out, specifically Comparative Examples 1 to 3, as described below: Comparative Example 1: Comparative Example 1 is based on Example 1, with the following adjustments: the operations of S9 to S13 are not performed, and other processes remain unchanged, that is, the SGC composite material is used as the silicon-based anode active material.

[0025] Comparative Example 2: Comparative Example 2 is based on Example 1, with the following adjustments: the modified silicon dispersion and the graphene dispersion are directly mixed, and then vacuum dried at 80°C for 12 hours to obtain a Si@GO composite material, which is used as a silicon-based anode active material.

[0026] Comparative Example 3: Commercial silicon-carbon powder is directly used as the silicon-based anode active material.

[0027] Performance test: The silicon-based anode active materials corresponding to Example 1 and Comparative Examples 1 to 3 were prepared into batteries, and then the charge and discharge performance tests were performed, as follows: (1) adding silicon-based anode active material, acetylene black and polyvinyl difluoride into N-methylpyrrolidone in a mass ratio of 8:1:1, stirring and mixing evenly to obtain a slurry; (2) coating the slurry onto copper foil, placing it at 120°C and vacuum drying it for 12 hours to obtain an electrode sheet; (3) Cut the electrode sheet into 1.54cm2 (1.4 cm in diameter) and use 400 N / cm 2 The electrode disc is compacted by force to ensure that the loading amount of silicon-based anode active material on the electrode disc is about 0.5 mg / cm 2 ; (4) Assemble CR2016 button cells in a glove box filled with high-purity Ar (more than 99.5%): use metal lithium sheets as counter electrodes, polypropylene film (Celgard2400) as separators, and 1 mol / L LiPF6 solution as electrolyte (LiPF6 solution is prepared by mixing ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1, and adding 2 v / v% of vinylene carbonate as an additive); (5) Using LANDCT2001A battery tester, test the battery at 0.25A·g -1 Electrochemical performance at current density.

[0028] The test results of the above test contents are shown in Table 1 below: Table 1

[0029] Result analysis: From the data in Table 1 above, it can be seen that the Ti3C2T x As a silicon-based anode active material, MXene&SGC composite material has significantly superior electrochemical performance. Compared with commercial silicon carbon powder, its cycle performance decay is relatively stable and has a longer cycle life cycle, indicating that Ti3C2T x MXene&SGC composite material can inhibit the deformation and damage of anode structure in the cycle process. Compared with SGC composite material, Ti3C2T x MXene nanosheet coating can significantly improve the electrochemical performance of the battery, which further shows that Ti3C2T x MXene nanosheets coating the SGC composite material can further provide a layer of protection for the SGC composite material and reduce the damage caused by volume expansion; at the same time, it can also reduce the breakage and repair process of the SEI film and ensure the stability of the SEI film; in addition, it can also provide excellent mechanical toughness to protect the silicon-based anode material, thereby increasing the strength and stability of the battery and preventing the battery from structural deformation and damage during the cycle process.

[0030] In summary, the Ti3C2T prepared by the present invention xMXene&SGC composite materials can reduce the structural deformation and damage of silicon-based anodes during the cycle process, while also reducing the breakage and repair process of the SEI film and protecting the stability of the SEI; as a silicon-based anode active material, it can greatly improve the electrochemical performance of the battery and has important practical significance.

[0031] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for reducing structural deformation and damage during the cycle of silicon-based anodes, characterized in that: By using Ti3C2T x MXene & SGC composites are realized as silicon-based anode active materials; the Ti3C2T x The MXene&SGC composite material has a layered structure, with Ti3C2T x MXene substrate, SGC interlayer and Ti3C2T x MXene top three-layer structure; Ti3C2T x The preparation method of MXene&SGC composite material is as follows: (1) dispersing nano-silicon into phenolic resin, and then utilizing the surface charge adsorption effect to make nano-silicon and graphene oxide adsorb and self-assemble to form gel, and then freeze-drying, grinding, carbonization treatment, and CVD treatment to obtain SGC composite material; (2) vacuum filtration is used to make Ti3C2T x MXene nanosheets were coated on the surface of SGC composites to obtain Ti3C2T x MXene&SGC composite materials.

2. A method for reducing structural deformation and damage during the cycle of a silicon-based anode according to claim 1, characterized in that: The Ti3C2T x The preparation method of MXene&SGC composite material specifically comprises the following steps: S1: slowly add 2-pentanol and 1,2-bis[(dimethylamino)dimethylsilyl]ethane to N-methylpyrrolidone, and stir for 15-60 minutes to obtain a mixed solution I; S2: adding nano silicon to the mixed solution I, stirring and mixing for 1-3 hours to obtain a modified silicon dispersion; S3: adding phenolic resin to N-methylpyrrolidone and stirring to dissolve the phenolic resin to obtain a phenolic resin solution; S4: mixing the modified silicon dispersion and the phenolic resin solution, stirring evenly to obtain a mixed solution II; S5: adding graphene oxide to N-methylpyrrolidone, stirring and mixing for 1-3 hours to obtain a 3-3.5 wt % graphene dispersion; S6: slowly adding the graphene dispersion into the mixed solution II to obtain a mixed solution III, and then freeze-drying the mixed solution to obtain an aerogel; S7: grinding the aerogel into a powder of 150-220 mesh to obtain a precursor powder; S8: placing the precursor powder into a tube furnace, and subjecting the precursor powder to carbonization treatment and CVD treatment to obtain an SGC composite material; S9: Ti3C2T x MXene nanosheets were added to N-methylpyrrolidone and stirred for 1-3 h to obtain 4-6 mg / mL Ti3C2T x MXene dispersion; S10: Take part of Ti3C2T x The MXene dispersion was dried and deposited by vacuum filtration to obtain Ti3C2T x MXene substrate; S11: adding the SGC composite material into deionized water and ultrasonically dispersing for 10-20 min to obtain an SGC dispersion; S12: Apply SGC dispersion evenly to Ti3C2T x On the MXene substrate layer, it is dried and deposited by vacuum filtration to obtain the SGC intermediate layer; S13: Take another Ti3C2T with the same volume as that in S10 x The MXene dispersion was evenly coated on the SGC middle layer and dried and deposited by vacuum filtration to obtain Ti3C2T x MXene top layer; get Ti3C2T x MXene&SGC composite materials.

3. A method for reducing structural deformation and damage during the cycle of a silicon-based anode according to claim 2, characterized in that: The volume ratio of the 2-pentanol, 1,2-bis[(dimethylamino)dimethylsilyl]ethane and N-methylpyrrolidone is 1:2:

9.

4. A method for reducing structural deformation and damage during the circulation process of a silicon-based anode according to claim 2, characterized in that: The ratio of the nano-silicon to the mixed solution I is 1 g:10 mL, wherein the particle size of the nano-silicon is 100 nm.

5. A method for reducing structural deformation and damage during the cycle of a silicon-based anode according to claim 2, characterized in that: The mass ratio of the nano-silicon, graphene oxide and phenolic resin is 10:1:

25.

6. A method for reducing structural deformation and damage during the cycle of a silicon-based anode according to claim 2, characterized in that: The freeze drying process is as follows: the mixed solution III is placed in a freeze dryer and freeze dried at -35 to -25°C for 5 to 10 days.

7. A method for reducing structural deformation and damage during the cycle of a silicon-based anode according to claim 2, characterized in that: The specific process of the carbonization treatment is: placing the precursor powder in a tubular furnace filled with Ar, heating from room temperature to 480-520° C. at a heating rate of 5° C. / min for 1-3 hours.

8. A method for reducing structural deformation and damage during the cycle of a silicon-based anode according to claim 2, characterized in that: The specific process of the CVD treatment is as follows: after the carbonization treatment, an Ar / CH4 mixed gas is introduced into the tubular furnace, and then the temperature is continuously raised to 850-900°C at a heating rate of 2°C / min and heated for 1-3h.

9. A method for reducing structural deformation and damage during the cycle of a silicon-based anode according to claim 7, characterized in that: The Ar / CH4 mixed gas is composed of Ar and CH4 mixed in a volume ratio of 1:

1.

10. A method for reducing structural deformation and damage during the cycle of a silicon-based anode according to claim 2, characterized in that: In S10 and S13, the Ti3C2T x The mass ratio of MXene nanosheets to SGC composites is 1:4.

Citation Information

Cited By

  • Silicon-carbon composite negative electrode material and preparation method and application thereof

    CN121460562A

  • A silicon-carbon composite anode material, its preparation method and application

    CN121460562B